Pengembangan Keterampilan Brand Awareness pada Pelaku Usaha Desa Pasirtanjung, Kecamatan Tanjungsari, Kabupaten Bogor - Damanik, Novitasari; Fajar Rakhman, Gumgum Gumelar; Yudhaningrum, Lupi (Universitas Negeri Jakarta, 2023)
Economic challenges extend beyond financial implications, influencing various facets of society. Consequently, addressing these issues is vital for national development. Empowering communities to become entrepreneurs is a key solution for fostering economic growth. Notably, brand awareness among business operators is a critical component in shaping public perception and recognition of their endeavors. Our community service initiative in Pasirtanjung Village, West Java, is tailored to the specific needs of this community. The village's business operators lack awareness of the significance of brand identity, evident in their businesses' absence of distinctive branding. In this context, our program centers on elevating brand awareness by enhancing entrepreneurial skills among local business operators. The training aims to bridge this awareness gap and facilitate the creation of distinctive brand identities for these enterprises. Crucially, our program yielded significant results, with pre-test scores (M=61.5, SD=19.8) differing significantly from post-test scores (M=71, SD=16.2); t(19)=-3.047, p=0.007. This underscores the effectiveness of our efforts in enhancing entrepreneurial skills and brand awareness within the Pasirtanjung community. In summary, our program addresses the specific needs of Pasirtanjung Village, where business operators currently lack brand awareness. Through enhanced entrepreneurial skills, we aspire to empower them to develop unique brand identities, ultimately contributing to their economic growth and community development.